Stabilization and formulation of a recombinant Human Cytomegalovirus vector for use as a candidate HIV-1 vaccine. Issue 44 (16th October 2019) - Kumru, Ozan S.; Saleh-Birdjandi, Soraia; Antunez, Lorena R.; Sayeed, Eddy; Robinson, David; van den Worm, Sjoerd; Diemer, Geoffrey S.; Perez, Wilma; Caposio, Patrizia; Früh, Klaus; Joshi, Sangeeta B.; Volkin, David B.
Abstract: Live attenuated viral vaccine/vector candidates are inherently unstable and infectivity titer losses can readily occur without defining appropriate formulations, storage conditions and clinical handling practices. During initial process development of a candidate vaccine against HIV-1 using a recombinant Human Cytomegalovirus vector (rHCMV-1), large vector titer losses were observed after storage at 4 °C and after undergoing freeze-thaw. Thus, the goal of this work was to develop candidate frozen liquid formulations of rHCMV-1 with improved freeze-thaw and short-term liquid stability for potential use in early clinical trials. To this end, a virus stability screening protocol was developed including use of a rapid, in vitro cell-based immunofluorescence focus assay to quantitate viral titers. A library of ∼50 pharmaceutical excipients (from various known classes of additives) were evaluated for their effect on vector stability after freeze-thaw cycling or incubation at 4 °C for several days. Certain additives including sugars and polymers (e.g., trehalose, sucrose, sorbitol, hydrolyzed gelatin, dextran 40) as well as removal of NaCl (lower ionic strength) protected rHCMV-1 against freeze-thaw mediated losses in viral titers. Optimized solution conditions (e.g., solution pH, buffers and sugar type) slowed the rate of rHCMV-1 titer losses in the liquid state at 4 °C. After evaluating various excipient combinations, three new candidate formulations were designed and rHCMV-1 stability was benchmarked against both the currently-used and a previously reported formulation. The new candidate formulations were significantly more stable in terms of reducing rHCMV-1 titer losses after 5 freeze-thaw cycles or incubation at 4 °C for 30 days. This case study highlights the utility of semi-empirical design of frozen liquid formulations of a live viral vaccine candidate, where protection against infectivity titer losses due to freeze-thaw and short-term liquid storage are sufficient to enable more rapid initiation of early clinical trials.